Investigating the roles and training of paediatric research nurses working across Europe: a questionnaire-based survey. Issue 1 (5th September 2017) - Veal, Gareth J; Malik, Salma; Lupo, Mariangela; MacFarlane, Susan; Lepola, Pirkko; Costello, Mary; Ceci, Adriana; Boué, Carine; Lecour, Charlotte; Otto, Annette; Rastegari, Maryam; Berry, Philip
Abstract : Background: The key role played by research nurses in coordinating clinical trials in a paediatric setting has developed in line with increasing complexities of trial design. A questionnaire-based survey was conducted to investigate the training of research nurses involved in paediatric trials across Europe, to identify potential training needs and compare roles across specialties and countries. Methods: A structured, cross-sectional questionnaire survey was used, with the aim of describing and quantifying research nurse experiences. The questionnaire was designed to cover four main areas of interest: demographics, training, clinical trial experience and research nurse roles/activities. Results: The questionnaire was completed by 341 respondents across 45 different specialties in 20 European countries. A higher percentage of research nurses within 3 years of taking up post were dissatisfied with the level of training received (16%), as compared with those in post for 3–6 years (8%) and >6 years (6%). There was a trend towards a higher percentage of respondents receiving self-funded training in mainland Europe, with reported values of 15%–20%, as compared with <5% in the UK and Ireland. Only 3% of research nurses prescribed investigational medicinal products in a clinical trial setting, with contrasting roles observed between countries. Conclusions: While high levels of training satisfaction were observed, 67% of respondents felt they would benefit from additional training in line with frequently changing practices. Currently, low levels of nurse prescribing are observed in a paediatric clinical trial setting across Europe. Appropriate research nurse training programmes should be promoted through national networks across Europe.